Vegetation Dynamics of Coastal Mangrove Forest: Vegetation dynamics of coastal mangrove forest - Miah, Md Abdul Quddus (Journal of the Asiatic Society of Bangladesh, Science, 2023)
In the man-made coastal forest, the vegetation dynamics of protected and unprotected coastal forests have been identified. This study examined and quantified the impacts of grazing on coastal vegetation. The investigation was conducted between January 2013 and December 2020. In a transect line, fifty-two distinct tree, herb, and shrub species were found in unprotected coastal areas, and 36 were found in protected areas. After eight years, the number of saplings (p=0.031), poles (p=0.030), and total (p=0.026) (seedling, sapling, and pole) regeneration were substantially different between protected and unprotected areas. The current study found no significant differences in regeneration and tree density after one and five years of establishing the protected zones. The greatest number of natural poles were found in protected and unprotected areas from 2017 to 2020. The changes in tree density were considerable (p=0.03) after eight years. From 2014 to 2017, the highest rate of seedling recruitment was 36622 to 43439 individuals observed in protected and unprotected areas. In protected areas, Excoecaria agallocha L. and Avicinnia officinalis L. had the most extensive regeneration coverage, and nine species of seedlings, saplings, and poles were seen in 2013 protected areas. After 8 years, E. agallocha had a 47.01% while Phoenix paludosa Roxb. had a 30.81% success rate. In 2020, seedlings of Pongamia pinnata L. (6.6%), Herietiera fomes Buch.-Ham. (5.5%), A. officnalis (5.30%) and the remaining six species were also seen. The species E. agallocha comprised 69.11% of the trees at Soner Char tree density, followed by Sonneratia apetala Buch.-Ham. (23.30%), P. paludosa (8.82%), H. fomes (3.43%), and the remaining two species in 2020. After eight years, the species S. apetala declined by 43.64% and 23.90% in protected and unprotected areas, respectively. The species Phoenix paludosa, H. fomes, A. officinalis, and Dolichandrone spathacea (L.F) Baill. Ex K. Schum. was found to replace S. apetala in protected areas. Grazing affects the natural recruitment stage of saplings and poles and tree stem density in unprotected areas. The observations assume that S. apetala will diminish due to climatic conditions, and E. agallocha will become the main dominating species in coastal areas. J. Asiat. Soc. Bangladesh, Sci. 49(2): 203-224, December 2023